Composition and abundance of macroplastic debris on the coast of Inobonto village, Bolaang Mongondow Regency, North Sulawesi, Indonesia - Yogi J. Anduk; Stephanus V. Mandagi; Ari B. Rondonuwu; Lawrence J.L. Lumingas; John L. Tombokan; Anneke V. Lohoo (Universitas Sam Ratulangi, 2026)
Coastal macroplastic pollution is a critical environmental issue, yet localized data, particularly from developing tropical regions, remain scarce. This study investigates the composition, abundance, and spatial distribution of macroplastic debris (>5 mm) on the coast of Inobonto Village, Bolaang Mongondow Regency, North Sulawesi, Indonesia. Sampling was conducted in February 2026 at three distinct coastal zones: an estuarine area (Location A), a residential shoreline (Location B), and a trading area adjacent to a traditional market (Location C). Using a 5 m × 5 m quadrat transect method following NOAA protocols, debris was collected, physically categorized, and classified into polymer types (HDPE, LDPE, PET, PP, PS, PVC, and Others). Statistical differences in abundance among locations were assessed using the Kruskal–Wallis test, followed by post-hoc Mann–Whitney comparisons. The results revealed that polypropylene (PP, 28.06%) and low-density polyethylene (LDPE, 23.72%) were the predominant polymer types across all sites. Total macroplastic abundance varied significantly by location, with the highest density recorded at the trading area (1.168 ± 0.663 items/m²), followed by the estuary (0.544 ± 0.154 items/m²) and the residential area (0.352 ± 0.232 items/m²). Notably, the trading area and estuary exhibited significantly higher debris loads compared to the residential zone (p < 0.05). These findings underscore that market-related activities and estuarine dynamics are primary drivers of macroplastic accumulation in Inobonto's coastal environment. This baseline data is essential for designing targeted, source-based waste reduction strategies and prioritizing coastal clean-up efforts in this region.